The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.5539/jas.v4n9p98
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of Yield Components in the PI 438489B by ‘Hamilton’ Recombinant Inbred Line (RIL) Population of Soybean [Glycine max (L.) Merr.]

Abstract: Yield is a multi-factorial trait determined by several genetic traits and highly correlated with important agronomic traits in many crops including soybean. [Glycine max (L.)]. Plant height, seed and pod numbers, and seed weight are all components of yield and polygenic in nature. The objective of this study was to identify quantitative trait loci (QTL) for days to germination, days to flowering, plant height, pod number, seed number, 100-seed weight, and total seed weight in soybean using the using the PI 438… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
2
5
0
Order By: Relevance
“…These correlation coefficients confirm the results obtained from Panthee et al (2007) where they found height being positively correlated with lodging (r=0.58) and lodging significantly correlated with maturity (r=0.17). Height was found being positively correlated with yield (r=0.2454); this estimate is close to the one obtained by Bobby et al (2012) which was r=0.307 and lower than the value obtained by Cicek et al (2006) of r=0.58.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…These correlation coefficients confirm the results obtained from Panthee et al (2007) where they found height being positively correlated with lodging (r=0.58) and lodging significantly correlated with maturity (r=0.17). Height was found being positively correlated with yield (r=0.2454); this estimate is close to the one obtained by Bobby et al (2012) which was r=0.307 and lower than the value obtained by Cicek et al (2006) of r=0.58.…”
Section: Discussionsupporting
confidence: 70%
“…According to Cicek et al (2006), we can expect an improvement in yield in taller plants compared to shorter ones. Also, a non-significant correlation between these two traits has been reported (Bobby et al, 2012;Diondra et al, 2008). Height has been negatively correlated with yield and this may be due to a positive correlation between height and lodging (Yuan et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…This RIL population was developed by the Agronomy Research Center, Iowa State University by Dr. Silvia Cianzio and was provided to us by Dr. Khalid Meksem of Southern Illinois University. The population was grown in two different seasons and locations (FSU campus, Fayetteville, NC -2010 andSaint Pauls, NC -2011) as described earlier (Ragin, Bazelle, Clark, Kantartzi, Meksem, Akond, and Kassem, 2012). RIL population and parental lines were harvested at maturity and seeds were dried for having samples for isoflavones analysis.…”
Section: Plant Materials Isoflavones Quantification and Data Analysismentioning
confidence: 99%
“…The number of pods per plant is one of the most agronomically important traits in soybean [ Glycine max (L.) Merri], and is strongly positively correlated with yield [ 1 ]. Numerous studies have mapped quantitative trait loci (QTLs) for pod number, with the aim of increasing the efficiency of breeding for higher yields [ 2 18 ]. Previously, 15 QTLs for total pod number per plant (TPNPP) were identified using recombinant inbred lines (RILs) derived from a cross between BARC-8 and Garimpo [ 2 ], while another study identified 12 TPNPP QTLs on chromosomes B1, C2, D1a, F, J, and N using a F 2:10 RIL population derived from a cross between Charleston and Dongnong 594 [ 3 ].…”
Section: Introductionmentioning
confidence: 99%